HUBUNGAN SISA KLOR DENGAN KELUHAN IRITASI KULIT DAN MATA PADA PEMAKAI KOLAM RENANG HOTEL DI WILAYAH KOTA YOGYAKARTA - Permana, teddy; Suryani, Dyah (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2013)
Background: Public places such as public baths and swimming pools are used as a gathering place by many people have potency to be a medium of disease transmission. Direct contact among visitors can transmit disease germs from one to the other visitors. Moreover, the contact can be a deployment medium of a disease. This study aimed to determine the relationship between chlorine residue with the complaints of skin and eye irritations of swimmingpool users in Yogyakarta hotels.Methods: The research was an observational analytic study by using cross sectional design. Sampling of the research uses systematic random sampling and consists of 48 respondents. Research tools used are questionnaires and laboratory tests. Data analysis uses univariate and bivariate analysis with a statistical test ChiSquare (X2).Results: Results of the study showed that 28 respondents (58.3%) have complaints and 20 respondents (41.7%) do not have complaints. From six water samples taken from swimming pool, 4 samples (66.7%) do not qualify and 2 samples (33.3%) are eligible. Bivariate analysis found that there was a significant relationship between chlorine residue with the complaints of skin and eye irritations of swimming pool users in Yogyakarta hotels (p = 0.038) smaller than alpha (? = 0.05), RP = 1,83. Conclusion: There was a relationship between residual chlorine with the complaints of skin and eye irritations of swimming pool users in Yogyakarta hotels.Keywords: Chlorine Residue, Skin and eye irritation complaints, Swimming Pool